Development of PISA-like Mathematics Problems within Personal-Context for Junior High School Students - Wisnu Siwi Satiti; Dungo Abid Alfatah; Fitri Umardiyah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Mathematics is a basic science that plays an important role in the development of science and technology. Mathematics is used as a means of thinking, developing reasoning power, logical, systematic, and critical thinking. One of the important aspects in mastering mathematics is the ability of students to apply mathematics in various situations in everyday life. Given the importance of mathematics education, various types of tests on students' mathematical abilities have been held, one of them is PISA study. PISA survey especially evaluates on students’ability on applying their mathematics knowledge in solving problems from real life context. However, based on result of latest PISA and severeal pervious studies, show that students in Indonesia are still weak in connecting mathematical concepts that have been studied with problems in everyday life. Therefore, it is necessary to increase the use of PISA-like Mathematics Problems within personal context, especially math problems that are relevant to the real-life context of Indonesian students. Due of that, in this study, the PISA-like Mathematics Problems within personal context will be developed. The type of research used is Research and Development (R&D) research, by adapting ADDIE model. The study was conducted at a class of XI-A SMPN 2 Sumobito Jombang. The results show that the PISA-like mathematics problems are valid and practical. Besides that, the results of the implementation of the PISA-like Mathematics Problems within personal context in this study showed that there were students who rarely even completed non-routine math problems such as the PISA-like mathematics problems.